O grupo operativo como instrumento de intervenção: integrando experiências sobre o fazer grupal - Menezes, Nayara Ruben Calaça Di (2021)
Group services are carried out in the most diverse institutions, such as clinics, schools, hospitals, rehabilitation centers, or even in churches and social spaces. The objective of this work is to analyze the group device as an instrument of intervention in different contexts, seeking to investigate how the operative group can favor the emergence of associative processes and forms of collective reflection about the stated task, as well as its potential for transformation and emancipation. Therefore, we carried out a bibliographical survey on the group theory proposed by Pichon-Rivière in the SciELO, Lilacs, PePSIC and Capes Journal Portal databases. We selected 77 articles published between 1992 and 2018. We divided the articles into four large groups, namely: (1) Theoretical Studies; (2) Health; (3) Education and (4) Social. Subsequently, we held seven group meetings referenced by Pichon-Rivière's theory and technique. Two were carried out with companions of children hospitalized in a Pediatric Intensive Care Unit, one with nursing technicians who work in the same Pediatric ICU and four in a Physical Education Faculty, one group with teachers, one with students, another with administrative technicians and a liaison group that included the participation of the three aforementioned categories. In the end, it was possible to know how the device of operative groups is being presented in academic works, as well as to relate theory with group practice, thus allowing to consider that the operative group, through moments of collective constructions, is able to facilitate processes of emancipation and reflection on the reality experienced.